2006
DOI: 10.1074/jbc.m600237200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity in p160/CREB-binding Protein Coactivator Complexes

Abstract: Ligand-induced transcription by nuclear receptors involves the recruitment of p160 coactivators such as steroid receptor coactivator 1 (SRC1), in complex with histone acetyltransferases such as CREB-binding protein (CBP) and p300. Here we describe the solution structure of a complex formed by the SRC1 interaction domain (SID) of CBP and the activation domain (AD1) of SRC1, both of which contain four helical regions (C␣1, C␣2, C␣3, and C␣3 in CBP and S␣1, S␣2, S␣2, and S␣3 in SRC1). A tight four-helix bundle is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 50 publications
2
64
0
Order By: Relevance
“…Over the past 10 years, a combination of biochemical, genetic, and structural experiments has conclusively identified relevant targets for some mammalian and yeast activators (e.g., Stevens et al 2002;Yang et al 2004;Green 2005;Sampietro et al 2006;Waters et al 2006;Thakur et al 2009;Herbig et al 2010;Jedidi et al 2010). In general, these targets are located in coactivator complexes and chromatin-remodeling or -modifying factors rather than in subunits of the general transcription factors.…”
Section: Activator Targetsmentioning
confidence: 99%
“…Over the past 10 years, a combination of biochemical, genetic, and structural experiments has conclusively identified relevant targets for some mammalian and yeast activators (e.g., Stevens et al 2002;Yang et al 2004;Green 2005;Sampietro et al 2006;Waters et al 2006;Thakur et al 2009;Herbig et al 2010;Jedidi et al 2010). In general, these targets are located in coactivator complexes and chromatin-remodeling or -modifying factors rather than in subunits of the general transcription factors.…”
Section: Activator Targetsmentioning
confidence: 99%
“…The NCBD:ACTR complex was the first documented example of an IDP that folds upon binding to another IDP in a process termed mutual synergistic folding (16). Structural studies of the complexes of NCBD and three of its ligands have shown that the complexes have fully compact and well defined globular structures, and that NCBD adopts at least two different ligand specific structures (16,19,20). This structural adaptability is a functional hallmark of the IDPs.…”
Section: Creb Binding Protein | Folding Upon Binding | Nmr Spectroscopymentioning
confidence: 99%
“…Upon binding to its physiological partners, the NCBD folds to form a bundle of three helices that differ in their topological arrangements in complexes with intrinsically disordered targets, such as the p160 nuclear coactivators ACTR (coactivator for thyroid and retinoid receptors) and SRC-1 and the p53 activation domain (18,54,55), and in the complex with the stably folded interferon regulatory factor IRF-3 (56). Detailed NMR and computational studies suggest that in the unbound state, the NCBD is flexible and fluctuates over an ensemble of conformations that includes both the ACTR/SRC-1-bound conformation and the IRF-3-bound conformation (57-61).…”
Section: Ncbd Interactionsmentioning
confidence: 99%